Anisocoria After Direct Light Stimulus is Associated with Poor Outcomes Following Acute Brain Injury - Doyle, Brittany R.; Aiyagari, Venkatesh; Yokobori, Shoji; Kuramatsu, Joji; Barnes, Arianna; Puccio, Ava; Nairon, Emerson B.; Marshall, Jade L.; Olson, Dai Wai M. (Neurocritical Care, 2024)
Background: Assessing pupil size and reactivity is the standard of care in neurocritically ill patients. Anisocoria observed in critically ill patients often prompts further investigation and treatment. This study explores anisocoria at rest and after light stimulus determined using quantitative pupillometry as a predictor of discharge modified Rankin Scale (mRS) scores. Methods: This analysis includes data from an international registry and includes patients with paired (left and right eye) quantitative pupillometry readings linked to discharge mRS scores. Anisocoria was defined as the absolute difference in pupil size using three common cut points (> 0.5 mm, > 1 mm, and > 2 mm). Nonparametric models were constructed to explore patient outcome using three predictors: the presence of anisocoria at rest (in ambient light); the presence of anisocoria after light stimulus; and persistent anisocoria (present both at rest and after light). The primary outcome was discharge mRS score associated with the presence of anisocoria at rest versus after light stimulus using the three commonly defined cut points. Results: This analysis included 152,905 paired observations from 6,654 patients with a mean age of 57.0 (standard deviation 17.9) years, and a median hospital stay of 5 (interquartile range 3–12) days. The mean admission Glasgow Coma Scale score was 12.7 (standard deviation 3.5), and the median discharge mRS score was 2 (interquartile range 0–4). The ranges for absolute differences in pupil diameters were 0–5.76 mm at rest and 0–6.84 mm after light. Using an anisocoria cut point of > 0.5 mm, patients with anisocoria after light had worse median mRS scores (2 [interquartile range 0–4]) than patients with anisocoria at rest (1 [interquartile range 0–3]; P <.0001). Patients with persistent anisocoria had worse median mRS scores (3 [interquartile range 1–4]) than those without persistent anisocoria (1 [interquartile range 0–3]; P <.0001). Similar findings were observed using a cut point for anisocoria of > 1 mm and > 2 mm. Conclusions: Anisocoria after light is a new biomarker that portends worse outcome than anisocoria at rest. After further validation, anisocoria after light should be considered for inclusion as a reported and trended assessment value.
CRIS-Team Scopus Importer:2024-07-05
Keywords: Anisocoria; Cranial nerves; Pupillary light reflex; Pupils